Leadership: A Systemic Practice in the Future of Business - González - Castro, Yolanda; Manzano - Durán, Omaira; Torres - Zamudio, Marleny (Universidad Francisco de Paula Santander, 2021)
This article with a qualitative approach of a documentary review type, discusses the evolution of leadership and divides it into three stages. From these ruptures, which emerged from the analysis of scientific articles and own reflections, leadership transcends and shows a new form of management. The document compares the theories of traits, the behavioral approach, the situational approach, transformational, cross-cultural and shared leadership. As a contribution to the knowledge about the evolution of leadership towards new theories, it is concluded that in the future systemic leadership should emerge as the result of a managerial evolution that is nourished by the contributions of the previous theories, transforming into a holistic strategy with a Shared vision of the elements that guided leadership through the years, and includes elements such as ethics, social responsibility, teamwork and holistic interaction.